Effect of ipragliflozin on carotid intima-media thickness in patients with type 2 diabetes: a multicenter, randomized, controlled trial. Issue 2 (29th October 2022) - Tanaka, Atsushi; Sata, Masataka; Okada, Yosuke; Teragawa, Hiroki; Eguchi, Kazuo; Shimabukuro, Michio; Taguchi, Isao; Matsunaga, Kazuo; Kanzaki, Yumiko; Yoshida, Hisako; Ishizu, Tomoko; Ueda, Shinichiro; et al.
Abstract: Aims: To examine the effects of a 24-month treatment with ipragliflozin on carotid intima-media thickness (IMT) in type 2 diabetes patients. Methods and results: In this multicenter, prospective, randomized, open-label, and blinded-endpoint investigator-initiated clinical trial, adults with type 2 diabetes and haemoglobin A1C (HbA1c) of 6.0–10.0% (42–86 mmol/mol) were randomized equally to ipragliflozin (50 mg daily) and non-sodium-glucose cotransporter-2 (SGLT2) inhibitor use of standard-care (control group) for type 2 diabetes and were followed-up to 24 months. The primary endpoint was the change in mean common carotid artery IMT (CCA-IMT) from baseline to 24 months. A total of 482 patients were equally allocated to the ipragliflozin ( N = 241) and control ( N = 241) groups, and 464 patients (median age 68 years, female 31.7%, median type 2 diabetes duration 8 years, median HbA1c 7.3%) were included in the analyses. For the primary endpoint, the changes in the mean CCA-IMT from baseline to 24 months were 0.0013 [95% confidence interval (CI), −0.0155–0.0182] mm and 0.0015 (95% CI, −0.0155–0.0184) mm in the ipragliflozin and control groups, respectively, with an estimated group difference (ipragliflozin-control) of −0.0001 mm (95% CI, −0.0191–0.0189; P = 0.989). A group difference in HbA1c change at 24 months was also non-significant between the treatment groups [−0.1% (95% CI, −0.2–0.1); P = 0.359]. Conclusion: Twenty-four months of ipragliflozin treatment did not affect carotid IMT status in patients with type 2 diabetes recruited in the PROTECT study, relative to the non-SGLT2 inhibitor-use standard care for type 2 diabetes.